International Commercial Mediation: Towards a Harmonized Legal Framework for Cross-Border Business Dispute Resolution - Ely Nursamsiah; Yuhelson Yuhelson; Supaphorn Akkapin (CV. Era Digital Nusantara, 2025)
Globalization has expanded cross-border trade while also increasing the number of international commercial disputes. Litigation, though authoritative, is often expensive, time-consuming, and complicated by different jurisdictional rules, which weakens legal certainty for businesses. Mediation provides a more efficient and flexible alternative that helps maintain business relationships. However, its effectiveness is still limited by fragmented national regulations, the voluntary nature of the UNCITRAL Model Law (2002), and limited ratification of the Singapore Convention on Mediation (2019). This study employs a normative legal approach, incorporating a comparative analysis of selected jurisdictions (the United States, the European Union, Singapore, and Indonesia), and is supported by secondary literature and institutional reports. Findings indicate that while Singapore has aligned its domestic law with international standards, most jurisdictions still treat international mediation ambiguously, weakening enforceability. Additional barriers include the shortage of qualified mediators, cultural biases toward litigation, and low business awareness. The novelty of this research lies in its integration of normative, socio-cultural, and institutional dimensions. Theoretically, it reinforces the transnational legal process framework; practically, it proposes a roadmap to strengthen mediation’s legitimacy through wider ratification, legal alignment, and capacity-building for mediators. The study concludes that a harmonized legal framework for international commercial mediation is not merely aspirational but a pressing necessity for global economic stability.